Risk for Acquiring Coronavirus Disease Illness among Emergency Medical Service Personnel Exposed to Aerosol-Generating Procedures - Aubrey Brown; Leilani Schwarcz; Catherine R. Counts; Leslie M. Barnard; Betty Y. Yang; Jamie M. Emert; Andrew Latimer; Christopher Drucker; John Lynch; Peter J. Kudenchuk; Michael R. Sayre; Thomas Rea (Emerging Infectious Diseases, 2021)
We investigated the risk of coronavirus disease (COVID-19) patients transmitting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to emergency medical service (EMS) providers, stratified by aerosol-generating procedures (AGP), in King County, Washington, USA, during February 16–July 31, 2020. We conducted a retrospective cohort investigation using a statewide COVID-19 registry and identified 1,115 encounters, 182 with ≥1 AGP. Overall, COVID-19 incidence among EMS personnel was 0.57 infections/10,000 person-days. Incidence per 10,000 person-days did not differ whether or not infection was attributed to a COVID-19 patient encounter (0.28 vs. 0.59; p>0.05). The 1 case attributed to a COVID-19 patient encounter occurred within an at-risk period and involved an AGP. We observed a very low risk for COVID-19 infection attributable to patient encounters among EMS first responders, supporting clinical strategies that maintain established practices for treating patients in emergency conditions.